The Phenomenology of Living with A Sibling with Special Needs - Bailey, Rhea R. (Jurnal Pendidikan Bitara UPSI, 2024)
Disabilities are diverse and these vary in severity. This phenomenological study attempted to generate data that answered the question of how siblings of individuals with special needs construed their lives in terms of a) fond experiences or advantages, and b) challenges or limitations. Data gathering was executed in-person and through online semi-structured interviews with siblings of individuals with disabilities who had high functional autism, Marfan Syndrome, and Down’s Syndrome. Findings showed that challenges were many and can be overwhelming. These are manifested in: dealing with unpredictable behavior and expressions of frustration, being disheartened over sibling’s inability to experience normal activities, bearing the stigma due to obvious physical limitations, managing their siblings’ limited ability to fully articulate needs, the dilemma of not doing enough for their sibling while attending to their own personal or family needs, having to absorb sibling’s depression, restrictions in going to places and engagement with peers, having to worry about leaving their sibling behind, coping with financial challenges, and resorting to self-harm in channeling frustrations. However, the participant’s current relationships with their siblings overcome these complexities and troubles. Thus, they still see their lives positively. In addition, the participants aspire that the general public understands that individuals with special needs have different abilities from which the community or general society can benefit from. This research is relevant as it sheds light on how home and community life can be viewed from the lens of a sibling with a family member who has special needs – their challenges, limitations, and their triumphs. They call for the awareness and participation of the community as it takes a home and a caring social network to support an individual with special needs.